2023
DOI: 10.1021/acscatal.3c00845
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Metal–Halogen Bonding for Hydrogen-Induced Acid Generation in Bifunctional Catalysis

Abstract: Within conventional bifunctional catalysts, active metal sites are associated with metal components, while acid sites are usually localized over oxide supports. The modification of metal sites by halogens provides an opportunity to generate acidity via the heterolytic dissociation of hydrogen directly over metal sites. Herein, we report the results of high-throughput screening of the combinations of different metals (Co, Ni, Ru, Pt, Pd, Rh) and halogens (Cl, Br, I) for acid site generation from hydrogen in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Transmission electron microscopy (TEM) images indicated that Pd NPs had excellent dispersion on Al 2 O 3 (Figure S3a, and Figure b), and the average size of the metal decorated by Cl species increased from 5.70 to 6.56 nm (Figure S3b and Figure c). High-resolution TEM (HRTEM) images showed a 0.22 nm lattice spacing, which was related to the (111) plane of metallic Pd NPs (Figure S3c and Figure d). , The Cl species were clearly located by high-angle annular dark-field scanning TEM (HAADF-STEM) and energy dispersive X-ray analysis (EDX) element mapping images (Figure e–i). As expected, a much more intense Cl EDX signal on Pd NPs was detected rather than on the Al 2 O 3 support.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) images indicated that Pd NPs had excellent dispersion on Al 2 O 3 (Figure S3a, and Figure b), and the average size of the metal decorated by Cl species increased from 5.70 to 6.56 nm (Figure S3b and Figure c). High-resolution TEM (HRTEM) images showed a 0.22 nm lattice spacing, which was related to the (111) plane of metallic Pd NPs (Figure S3c and Figure d). , The Cl species were clearly located by high-angle annular dark-field scanning TEM (HAADF-STEM) and energy dispersive X-ray analysis (EDX) element mapping images (Figure e–i). As expected, a much more intense Cl EDX signal on Pd NPs was detected rather than on the Al 2 O 3 support.…”
Section: Resultsmentioning
confidence: 97%
“…High-resolution TEM (HRTEM) images showed a 0.22 nm lattice spacing, which was related to the (111) plane of metallic Pd NPs (Figure S3c and Figure 5d). 38,39 The Cl species were clearly located by high-angle annular dark-field scanning TEM (HAADF-STEM) and energy dispersive X-ray analysis (EDX) element mapping images (Figure 5e−i). As expected, a much more intense Cl EDX signal on Pd NPs was detected rather than on the Al 2 O 3 support.…”
Section: Characterization Ofmentioning
confidence: 99%
“…At present, DMF is principally synthesized in the presence of exogenous hydrogen and substantial achievements have been accomplished in the HDO of HMF to DMF with molecular hydrogen, affording high DMF yield when using various noble ( e.g., Pd, Pt, and Ru ) and non-noble metal catalysts ( e.g., Co, , Ni, and Cu ). Compared to the H 2 -driven HDO process, catalytic transfer hydrodeoxygenation (CTHDO) with alcohols as the hydrogen donor can be a more convenient and safer alternative, which has merely received cursory attention for the HMF-to-DMF transformation.…”
Section: Introductionmentioning
confidence: 99%